CONSUMPTION AND UNPREDICTABILITY IN MODERN AMERICAN CULTURE: DON DELILLO'S PRAGMATIC INTERPRETATION OF CONSUMER CULTURE AND UNRELIABILITY IN WHITE NOISE - Zakia Naeem; Nokhaiz Zahra (International Journal of Contemporary Issues in Social Sciences, 2024)
This article aims to do a postmodern examination of Don DeLillo's science fiction novel White Noise, that explores the absurdity of existence and people's hypocritical interactions with one another. This article's goal is to expose American popular culture, which is heavily reliant on consumerism, by theoretically dismantling postmodern components. The study's focus has remained on the modern way of living, where people find fulfilment in fabricating a false sense of self and giving their own self-constructed realities significance. Additionally, this essay exposes the postmodern diversions that characters in the book engage in through media, TV, radio, and technology. These distractions keep people from focusing on life's real issues. In addition, the novel's central theme—which illustrates the uncertainties of life—is death. During the entire book, it conjures up a strange and gloomy atmosphere. The research gap will be filled by this paper's critical analysis of all the ways that consumerism has affected American society as it is presented in DeLillo's novel White Noise, as well as the fallibility of many of the sources and goods he mentions.